Research on structure characteristics of the helium-lubricated spiral grooved thrust bearing for helium turbine expander. Issue 1 (February 2021) - Zhang, X H; Peng, N; Dong, B; Li, KR; Liu, L Q
Abstract: The helium-lubricated spiral grooved thrust bearing of helium turbo expander was studied by numerically simulating the steady-state non-linear Reynolds equation, the Reynolds equation of the pressure was solved by finite difference method (FDM), the film pressure distribution is calculated iteratively by MATLAB program, the structural parameters including the spiral angle, the groove length ratio, the groove width ratio influenced on the static characteristics were analyzed. The results show that: The bearing loading capacity of helium lubricated spiral grooved thrust gas bearing is lower than that of air lubricated bearing under the same conditions; The viscosity of the lubricant only affects the gas carrying capacity of the thrust disc when the spiral groove is on the bearing, while the density of the lubricant has a greater influence on the bearing loading capacity; When the spiral groove is designed on the rotor thrust disc, the bearing loading capacity of the spiral grooved thrust bearing increases by 6% on average compared with that of the spiral groove on the bearing.